Model predictive control-based DC overcurrent protection method for 400 Hz ground power unit - Que, Son Tran; Anh, Vuong Nguyen; Van, Diep Huynh; Quang, Dich Nguyen; Kien, Trung Nguyen (International Journal of Power Electronics and Drive Systems (IJPEDS), 2025)
This paper presents a new configuration of 400 Hz inverters designed for ground power units (GPU) in the aerospace field. In this model, instead of using rectifiers fed by the AC electric grid, a lithium battery system is employed due to its advantages, especially in improving the flexibility and reliability of the power supply. A model predictive control (MPC) strategy with the extended cost function is proposed for the current loop, which is expected to restrict the DC current avoiding the battery overcurrent that causes the system interrupted by the battery management system (BMS), improving the overall system dynamic. The mathematical relationship between battery current and inductor current has also been derived to support the design of the MPC controller. A proportional resonant (PR) controller is performed for the outer loop to control fundamental voltages, and compensate for the harmonic distortions. A comprehensive simulation model is initially created in the MATLAB environment and subsequently validated through hardware-in-the-loop (HIL) testing to assess the performance of the proposed control technique. The results obtained demonstrate the effectiveness of the control scheme in terms of DC-link battery current being controlled at an acceptable value, high-quality voltage is provided at the output with harmonic distortions compensated by PR controller.